ANALISIS FAKTOR JUMLAH PENGUNJUNG OBYEK WISATA SRAMBANG PARK NGAWI JAWA TIMUR - Erni Mukti Rahayu; Joko Triwanto; Mochamad Chanan; Oktavia - (Jurnal Hutan Tropis, 2021)
The aim of this researchs to know the factors that influence number of visitors in Srambang Park tourist attraction. The factors include gender, age of visitors, level of education, family dependents, occupation, income, service, security, cleanliness, facilities, distance. Purposive sampling data collection technique, respondents in this study visitors to the Srambang Park tour with a total of 35 respondents. The data obtained in the field were analyzed using SPSS correlation analysis. The results of the analysis show that the factors that affect the number of visitors are categorized into a) very low (0.00-0.199); gender, occupation, income, service, b) quite strong (0.40-0.599); visitor age, education level, security, c) strong (0.60-0.799); facilities, distance. The management of the Srambang Park area pays attention to environmental sustainability, through planting, conservation of springs and waste management. The existence of Srambang Park tourism object is able to improve the socio-economy of the surrounding community through direct involvement as Srambang Park employees, becoming a motorcycle taxi driver to tourist sites and selling in the Srambang Park area.